Controls on biogenic methane formation in Cherokee basin coalbeds, Kansas - Wilson, Brien (Kansas State University, 2015)
The Cherokee basin in southeastern Kansas is a declining coalbed methane (CBM) field where little is known about how the CBM formed, the extent to which it continues to form, and what factors influence its formation. An understanding of methanogenic processes and geochemistry could lead to potential enhancement of methane formation in the basin. The objectives of this project are to (1) determine the pathway of methane formation and (2) determine whether geochemistry has influenced gas formation. In order to reach the objectives, we analyzed formation water geochemistry, production history, and gas composition and isotopes. Post Rock Energy Corporation gave us access to 16 wells for sampling purposes. We collected gas samples in Isotubes® for compositional and isotopic analyses at a commercial laboratory. We analyzed major ion chemistry from formation water using standard methods. Co-produced water samples we collected are Na-Cl type with total dissolved solids content ranging from 35,367 to 91,565 mg/L. TDS tended to be highest in samples collected from wells with greater total depth. The pH and temperature of sampled water averaged 7.0 and 19°C with an alkalinity ranging from 3.33 to 8.59. Gas dryness and δ¹³C CH[subscript 4] range from 196 to 4531 and -69.95 to -56.5, respectively, which indicate that methane is being produced biologically. Comparing the δ¹³C CH[subscript 4] to the δD CH[subscript 4], which ranges from -228.2 to -217.2, suggest that the primary pathway of methanogenesis is H[subscript 2]/CO[subscript 2] reduction. We calculated Δ (the difference between δ values) in order to correlate isotope data to produced water chemistry. Samples ΔD and Δ¹³C values range from -189.1 to -168.7 and 61.52 to 69.99. Calculated ΔD[subscript CH4-H2O] and Δ¹³C[subscript CO2-CH4] values approach the range for the acetate/methyl pathways as Clˉ concentration increases, potentially indicating a slight shift in methanogenic pathway in deeper, more saline portions of the basin. The culturing results revealed that living methanogens are still able to utilize H[subscript 2], acetate, and methanol present in co-produced formation water from all tested wells.
Keywords: Geology; Geochemistry; Natural gas; Cherokee basin; Methanogenesis; Biogeochemistry (0425); Geochemistry (0996)